Control Quality S.A. - Tateishi Saito, Víctor (2003)
This work studies the case of the multinational company Control Quality Ltd., leader in quality control in mining and food products. And the case of Oscar Perez who assumes the supervision of one of the laboratories whose main function is to request materials for the proper functioning of their premises.